Control del ciclo biológico del aedes aegypti como estrategia para minimizar la transmisión de la enfermedad del zika - Minuche Moreno, Bernarda Paulette (My University, 2018)
Zika is a disease known in recent years for its involvement in people, Aedes aegypti is the main species of mosquito involved in its transmission. A literature review was made on the subject where it was evidenced that the main entities in charge of surveillance and control are the WHO worldwide, the Ministry of Health at the national level, and the local SNEM, who fight for control and evaluate the outbreak conditions to maintain the health and quality of life of the population. Once this information was known, a strategy of awareness and education was developed, consisting of two tactics of chemical control by means of fumigations authorized by the WHO, and talks of awareness workshops to indicate the processes of mosquito growth and actions to intervene in their reproduction. Aedes aegypti achieves a remarkable dispersion in the world, for this reason there have been important epidemic outbreaks of the disease in many countries. In order to control the vector, the participation of the zone to intervene is essential, through a dynamic process developed specifically for education on the change of habits in their lifestyle, avoiding the accumulation of stagnant water and collaborating with fumigations.
El zika es una enfermedad conocida en los últimos años por su afectación en las personas, el Aedes aegypti es la principal especie de mosquito involucrada en su transmisión. Se realizó una revisión bibliográfica acerca del tema en donde se evidencio que los principales entes encargados de la vigilancia y control son la OMS a nivel mundial, Ministerio de Salud a nivel nacional, y la SNEM nivel local, quienes luchan por el control y evalúan las condiciones del brote para mantener la salud y la calidad de vida de la población. Conocida esta información se desarrolló una estrategia de conciencia y educación, que consiste en dos tácticas de control químico por medio de fumigaciones autorizadas por la OMS, y charlas talleres de conciencia para indicar los procesos de crecimiento del mosquito y acciones para intervenir en su reproducción. Aedes aegypti logra una notable dispersión en el mundo, por ello se han presentado importantes brotes epidémicos de la enfermedad en numerosos países. Para el control del vector es indispensable la participación de la zona a intervenir, mediante un proceso dinámico elaborado específicamente para la educación sobre el cambio de hábitos en su estilo de vida, evitando la acumulación de agua estancada y colaborando con las fumigaciones.
Keywords: ZIKA; ESTRATEGIA; AEDES AEGYPTI; CONTROL